Al-Ilâl Wa Al-Ibdâl Fî Sûrat Fâthir Wa Al-Istifâdah Minhâ Fî Ta’lîmi Ilmu Ash-Shorf - Laila Mardhiyah (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2020)
تهدف هذه الدراسة إلى التعرف على وجود الكلمات المشتملة على الإعلال والإبدال في سورة فاطر، ومعرفة نوع لكل الكلمات، ولاستفادة من كشفها في تعليم علم الصرف. وسلكت الدراسة على المنهج الوصفي التحليلي، وذلك بتتبع الكلمات المشتملة على الإعلال والإبدال في سوةر فاطر، وجمعها، وتصنيفها، وعرضها والاستنتاج. أسفرت الدراسة الحالية النتائج التالية: أن في سورة فاطر وردت الكلمات المشتملة على الإعلال والإبدال بجميع أنواعها من القلب، والحذف، والنقل، والتسكين، واختلاط بين نوعين وكلها 79 كلمة، بالتفصيل 76 كلمة تحتوي على الإعلال وثلاث كلمات تحتوي على الإبدال. وأن من التعرف على الكلمات المشتملة على الإعلال والإبدال في سورة فاطر يمكن لمعلم اللغة العربية الاستفادة في تعليم علم الصرف، حيث إنه يسهل المعلم في تعليم قواعد الإعلال والإبدال بالنموذج من الكلمات الواردة في سورة فاطر، ويسهل المتعلم في فهم علم الصرف خاصة قواعد الإعلال والإبدال وعند إرادة مراجعته. The purpose of this research is to find out the existence of words that consisted of al-i’lal wa al-ibdal in Fathir verse, and to analyzed the kind of al-i’lal wa al-ibdal, and knowing the benefit of this science in process learning ash-shorf. The urgency of al-i'lal wa al-ibdal in knowing the origin of words in Arabic that led to the writing of this research. The study used descriptive-analysis method, by tracing the words consisted of al-i’lal wa al-ibdal in Fathir verse, collecting data, analysing the kind of al-i’lal wa al-ibdal in every word, classifying data, explosing data in the table and conclusions data. This study proved the existence of the words that consisted of al i’lal wal ibdal in Fathir verse. The number of words reaches 79words from 31 ayat, there are 76 words consisted of al-i’lal and 3 words consisted of al-ibdal in spells. Then, by knowing the existence of words that consisted of al-i’lal wa al-ibdal in Fathir verse be able to ease Arabic Language teacher espcially study of Arabic in study proccess. And ease student to understand kaidah al-i’lal wa al-ibdal by example word that consisted of al-i’lal wa al-ibdal in Fathir verse.